Development and validation of an LC–MS/MS method for the determination of hinokiflavone in rat plasma and its application to a pharmacokinetic study. (18th September 2016) - Yin, Ruofeng; Xiong, Kun; Wen, Simin; Wang, Yuanyi; Xu, Feng
Abstract: Hinokiflavone has drawn a lot of attention for its multiple biological activities. In this study, a sensitive and selective method for determination of hinokiflavone in rat plasma was developed for the first time, using liquid chromatography–tandem mass spectrometry (LC–MS/MS). Amentoflavone was used as an internal standard. Separation was achieved on a Hypersil Gold C18 column with isocratic elution using methanol–water (65:35, v /v) as mobile phase at a flow rate of 0.3 mL/min. A triple quadrupole mass spectrometer operating in the negative electrospray mode with selected reaction monitoring was used to detect the transitions of m/z 537 → 284 for hinokiflavone and m/z 537 → 375 for IS. The LOQ was 0.9 ng/mL with a linear range of 0.9–1000 ng/mL. The intra‐ and inter‐day accuracy (RE%) ranged from −3.75 to 6.91% and from −9.20 to 2.51% and the intra‐ and inter‐day precision (RSD) was between 0.32–14.11 and 2.85–10.04%. The validated assay was successfully applied to a pharmacokinetic study of hinokiflavone in rats. The half‐life of drug elimination at the terminal phase was 6.10 ± 1.86 h, and the area under the plasma concentration‐time curve from time zero to the time of last measurable concentration and to infinity values obtained were 2394.42 ± 466.86 and 2541.93 ± 529.85 h ng/mL, respectively.